RELASI PERSIA DAN NUSANTARA PADA AWAL ISLAMISASI: Sebuah Kajian Awal Pengaruh Persia dalam Politik Aceh - Hilmy Bakar Almascaty (Media Syari'ah, 2017)
This article aims to examine the relationship between Persian and Nusantara in early years of Islamisation. The author argued that there is a strong evindence about the influence of Persian in Aceh. In this study, I investigated the history of Islamic Kingdom in Bireuen. By saying this, the essay opened the debate of the coming of Islam to the Archipelago, then discussed the history of Kerajaan Jeumpa. It concludes that Persian and Shi’ite played important role in Aceh.